2010
DOI: 10.1111/j.1749-6632.2010.05507.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction of regulator of G protein signaling‐2 with melanin‐concentrating hormone receptor 1

Abstract: Melanin-concentrating hormone receptor 1 (MCHR1) is a G protein-coupled receptor (GPCR) highly expressed in the central nervous system. MCHR1 mediates many physiological functions including energy homeostasis and emotional processing. By acting as GTPase-activating proteins, regulators of G protein-signaling (RGS) proteins are negative modulators of GPCRs. We previously elucidated that RGS8 of the B/R4 RGS subfamily potently inhibits the action of both Galphaq- and Galphai/o-dependent MCHR1 signaling. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…RGS5 may also have differential efficacy toward certain G protein-receptor combinations. Although most of the RGS proteins in the R4 subfamily bind G␣ i and G␣ q family members promiscuously, there is substantial evidence for direct interactions with GPCRs (44,45), which may specify selectivity for certain receptor-G protein combinations. A previous study found that chemotaxis of neutrophils elicited by fMLP, but not chemokines, is partially dependent on G␣ q (46).…”
Section: Rgs5 and Neutrophil Migrationmentioning
confidence: 99%
“…RGS5 may also have differential efficacy toward certain G protein-receptor combinations. Although most of the RGS proteins in the R4 subfamily bind G␣ i and G␣ q family members promiscuously, there is substantial evidence for direct interactions with GPCRs (44,45), which may specify selectivity for certain receptor-G protein combinations. A previous study found that chemotaxis of neutrophils elicited by fMLP, but not chemokines, is partially dependent on G␣ q (46).…”
Section: Rgs5 and Neutrophil Migrationmentioning
confidence: 99%
“…MCH-1R is widely distributed in the central nervous system and is particularly concentrated in regions that are involved in rewarding behavior, feeding behavior, and metabolic regulation . The distribution of the MCH-2R receptor is less clear . Behavior studies have demonstrated a physiological role of the MCH system in regulating food intake .…”
Section: Introductionmentioning
confidence: 99%
“…2 The distribution of the MCH-2R receptor is less clear. 8 Behavior studies have demonstrated a physiological role of the MCH system in regulating food intake. 4 Acute central administration of MCH or MCH-1R synthetic agonists leads to a rapid and significant increase in food intake in rodents.…”
Section: Introductionmentioning
confidence: 99%